State Aid to Electricity Producers: National and EU Law Aspects - Anita Rodiņa; Dārta Ūdre (Law: Journal of the University of Latvia)
At European Union level, there is a detailed regulatory framework allowing Member States to introduce state aid. State aid is always granted for a specific purpose and helps Member States to achieve their common objectives. The energy sector is being moved towards reaching targets for both energy efficiency and climate neutrality, with a gradual withdrawal from fossil fuels. However, it is not always easy to align these targets at Member State level and to create the appropriate national regulatory framework. Therefore, this article in the light of the two most recent judgements of the Constitutional Court of the Republic of Latvia (hereinafter – Constitutional Court), analyses the importance of a fixed term of state aid for electricity production and some aspects of state aid for biogas cogeneration plants, including the development of EU law perspective. The article also examines the impact of the enforcement of the Constitutional Court’s judgments in the area of state aid in Latvia and explains the emerging concept of environmental constitutionalism.